Just Mercy : A Story of Justice and Redemption - Stevenson, Bryan (New York : Spiegel & Grau, 2019)
The founder of the Equal Justice Initiative in Montgomery, Alabama, recounts his experiences as a lawyer working to assist those desperately in need, reflecting on his pursuit of the ideal of compassion in American justice.
Introduction: Higher ground -- Mockingbird players -- Stand -- Trials and tribulation -- The old rugged cross -- Of the coming of John -- Surely doomed -- Justice denied -- All God's children -- I'm here -- Mitigation -- I'll fly away -- Mother, mother -- Recovery -- Cruel and unusual -- Broken -- The stonecatchers' song of sorrow -- Epilogue.
Includes bibliographical references (pages 323-340) and index.
Keywords: Stevenson, Bryan; Equal Justice Initiative; Social reformers -- Biography; Lawyers -- Biography; Criminal justice, Administration of -- United States; Discrimination in criminal justice administration -- United States